Alterations of the fecal and vaginal microbiomes in patients with systemic lupus erythematosus and their associations with immunological profiles - Ling, Zongxin; Cheng, Yiwen; Gao, Jie; Lei, Wenhui; Yan, Xiumei; Hu, Xiaogang; Shao, Li; Liu, Xia; Kang, Runfang (Frontiers in Immunology, 2023)
Backgrounds: Exploring the human microbiome from multiple body niches is beneficial for clinicians to determine which microbial dysbiosis should be first targeted. We aim to study whether both the fecal and vaginal microbiomes disrupt in SLE patients and whether they are correlated, as well as their associations with immunological features. Methods: A group of 30 SLE patients and 30 BMI-age matched healthy controls were recruited. Fecal and vaginal samples were collected, 16S rRNA gene sequencing to profile microbiomes, and immunological features were examined. Results: Distinct fecal and vaginal bacterial communities and decreased microbial diversity in feces compared to the vagina were found in both SLE patients and controls. Differed bacterial community was found in patients’ feces and vagina. Compared to the controls, SLE group had slightly lower bacterial diversity in their gut were accompanied by significantly higher bacterial diversity in their vagina. The top predominant bacteria differed between feces and vagina in any group. Eleven genera differed in patients’ feces, such as Gardnerella and Lactobacillus increased, whereas Faecalibacterium decreased. Almost all of the thirteen genera differed in SLE patients’ vagina showing higher abundances, except for Lactobacillus. Three genera in feces and 11 genera in vagina identify biomarkers for SLE patients. The distinct immunological features were only associated with patients’ vaginal microbiome, such Escherichia−Shigella was negatively associated with serum C4. Conclusions: Although SLE patients had fecal and vaginal dysbiosis, dysbiosis in vagina was more obvious than that in feces. Additionally, only the vaginal microbiome interacted with patients’ immunology features.